Preventing Dropouts in Higher Education: Design of an early warning system - Cuttica, Mariela (2025)
Low graduation rates, increasing labor market demands for highly qualified and professionally trained workers, and evidence of both private and public benefits associated with a more educated population, are some of the warning signs highlighting the need to prevent dropout in higher education. The significant gap between those who access, persist, and complete higher education in Argentina has prompted the development of a proposal for an Early Warning System (EWS). This study aims to characterize higher education students at risk of dropping out and is structured into three main stages: (i) Proposal of risk factors for dropout in higher education, (ii) Proposal for improving the use of administrative data and Information Systems for Educational Management, and (iii) Proposal of warning indicators for early detection. Ten indicators were designed following the Context-Input-Process-Product model developed by OREALC/UNESCO. Policies aimed at supporting vulnerable groups are crucial to expanding access to higher education and promoting equal opportunities. In this context, the proposed EWS contributes to the identification of risk factors and their potential impact on student retention, providing tools for the development of intervention strategies. This study represents a contribution to educational management by facilitating the early identification of factors associated with dropout and enhancing institutional responses to these challenges.